Fusion with Promiscuous Gα16 Subunit Reveals Signaling Bias at Muscarinic Receptors - Randáková, Alena; Nelic, Dominik; Hochmalová, Martina; Zimčík, Pavel; Mulenga, Mutale Jane; Boulos, John; Jakubík, Jan (International journal of molecular sciences, 2021)
A complex evaluation of agonist bias at G-protein coupled receptors at the level of G-protein classes and isoforms including non-preferential ones is essential for advanced agonist screening and drug development. Molecular crosstalk in downstream signaling and a lack of sufficiently sensitive and selective methods to study direct coupling with G-protein of interest complicates this analysis. We performed binding and functional analysis of 11 structurally different agonists on prepared fusion proteins of individual subtypes of muscarinic receptors and non-canonical promiscuous α-subunit of G16 protein to study agonist bias. We have demonstrated that fusion of muscarinic receptors with Gα16 limits access of other competitive Gα subunits to the receptor, and thus enables us to study activation of Gα16 mediated pathway more specifically. Our data demonstrated agonist-specific activation of G16 pathway among individual subtypes of muscarinic receptors and revealed signaling bias of oxotremorine towards Gα16 pathway at the M2 receptor and at the same time impaired Gα16 signaling of iperoxo at M5 receptors. Our data have shown that fusion proteins of muscarinic receptors with α-subunit of G-proteins can serve as a suitable tool for studying agonist bias, especially at non-preferential pathways.
Keywords: molekulární konformace; Inhibitory Concentration 50; CHO buňky; signální transdukce; Isoxazoles; křečci praví; Molecular Conformation; Signal Transduction; AMP cyklický; Humans; Oxotremorine; Recombinant Fusion Proteins; GTP-Binding Protein alpha Subunits, Gq-G11; non-canonical signaling; proteiny vázající GTP - alfa-podjednotky Gq-G11; Protein Binding; fusion proteins; inhibiční koncentrace 50; lidé; receptory muskarinové; zvířata; CHO Cells; Cyclic AMP; isoxazoly; Cricetulus; simulace molekulární dynamiky; Molecular Dynamics Simulation; rekombinantní fúzní proteiny; vazba proteinů; kvartérní amoniové sloučeniny; muscarinic receptors; Cricetinae; Receptors, Muscarinic; Quaternary Ammonium Compounds; oxotremorin; Animals; signaling bias